Clinically Translatable Transcrocetin Delivery Platform for Correction of Tumor Hypoxia and Enhancement of Radiation Therapy Effects. Issue 12 (1st January 2023) - Diringer, Marie‐Charlotte; Coliat, Pierre; Mathieu, Clélia; Laurent, Nina; Mura, Carole; Banerjee, Mainak; Zhu, Chen; Grabowska, Anna; Ritchie, Alison; Clarke, Philip; Bernard, Alexandre; Vit, Claire; et al.
Abstract: Improving the tumor reoxygenation to sensitize the tumor to radiation therapy is a cornerstone in radiation oncology. Here, the pre‐clinical development of a clinically transferable liposomal formulation encapsulating trans sodium crocetinate (NP TSC) is reported to improve oxygen diffusion through the tumor environment. Early pharmacokinetic analysis of the clinical trial of this molecule performed on 37 patients orient to define the optimal fixed dosage to use in a triple‐negative breast cancer model to validate the therapeutic combination of radiation therapy and NP TSC. Notably, it is reported that this formulation is non‐toxic in both humans and mice at the defined fixed concentration, provides a normalization of the tumor vasculature within 72 h window after systemic injection, leads to a transient increase (50% improvement) in the tumor oxygenation, and significantly improves the efficacy of both mono‐fractionated and fractionated radiation therapy treatment. Together, these findings support the introduction of a first‐in‐class therapeutic construct capable of tumor‐specific reoxygenation without associated toxicities. Abstract : A liposome‐based nanoparticle encapsulating transcrocetin (NP TSC) acts as a radiosensitizer. The therapeutic concentration and dosage are identified based on Phase I clinical trial results and pre‐clinical validation is conducted in triple negative breast cancer mouse model. NP TSC provides a transient reoxygenation of the tumor (up to 48 h post‐treatment) and a normalization of the neovasculature.